Variation Characteristics of Water Level in Poyang Lake since 2000 - ZHOU Manning; ZHAO Junkai; YOU Meiling; DU Pengfei; YANG Wenfei; LIU Mingjuan; ZHANG Yujin (Renmin Zhujiang, 2025)
In recent years, under the influence of both natural factors and human activities, extreme hydrological events occur frequently in the Poyang Lake Basin, causing abnormal changes in water levels in the Poyang Lake. The water level data of Xingzi Gauge Station from 2000 to 2023 were collected, and the trend, mutability, and periodicity of the water level in the Poyang Lake from 2000 to 2023 were analyzed using Mann-Kendall trend test, sliding t test, ordered clustering, and wavelet analysis. The results show that from 2000 to 2023, the annual and flood-season water levels in the Poyang Lake Basin show an insignificant decline trend and exhibit discontinuity points in 2005. The average water level in the Poyang Lake within the whole year and the flood season has a significant period of 8–9 years. The water level in the dry season has a short period of significant oscillation, and there is a main period of 3–5 years. The variation range of the annual maximum water level of the Poyang Lake in terms of month narrows and is concentrated in June to July; the annual maximum water level appears earlier, and the concentration is stronger. The results can provide scientific reference for flood control, drought resistance, and water resources management in the Poyang Lake Basin.